Application of carbon nanotubes (CNT) on the computer science and electrical engineering: A review - Hossein Kardan Moghaddam; Mohamad Reza Maraki; Amir Rajaei (Institute of Advanced Engineering and Science, 2020)
In recent years, dimensions and sizes of components and parts in the computer and electronic industries have been steadily reducing, as they are now considered very tiny tools and there is always a need to store and process information stronger. Nanotubes have poor magnetic properties. If nanotubes are covered by ferromagnetic nanoparticles, their magnetic properties can be improved and they can be used in the manufacture of nanoelectronic devices in the computer and electronic industries. In addition to reviewing the structure and properties of materials made using different nanomaterials for use in the computer and electronic industries, the present paper aimed to study different applications of nanomaterials, especially carbon nanotubes, in the manufacture of electronic devices. The present study showed that the corporation of nanomaterials into electronic devices is a promising approach for future applications which can revolutionize the computer industry.